Characteristics of Eco-Friendly Marker Ink by Utilizing Natural Dyes From Noni Leaf Extract (Morinda Citrifolia L.) - Idha Silviyati; Hilwatullisan; Rusdianasari; Mujiyanti, Apri; Nainggolan, Hetty S (International Journal of Research in Vocational Studies (IJRVOCAS), 2024)
Marker ink created from natural ingredients can be used as an alternative to ink with high VOC (Volatile Organic Compound) levels, which can be harmful to one's health. Noni leaf extract includes tannins, which can be utilized as a basic dye/pigment in marker ink. The goal of this study is to use natural dyes derived from noni leaf extract as a replacement for synthetic ink VOC and as an innovation in green marker ink. The study was undertaken with various adjustments, including the inclusion of noni leaf tannins (0.6 gr, 0.8 gr, 1.0 gr, 1.2 gr, 1.4 gr) and gum arabic (4 gr, 5 gr). The analytical findings of the best arker ink products are presented in formula 5, which includes tannins mass 1.4 gr and gum arabic mass 4 gr, with a viscosity of 3.1 cp, density of 1.14 g/ml, pH 6, and concentrated pigment production. Based on these findings, marker ink products fulfill the quality standards of the SNI 06-1567-1999 test.